(untitled) (Baghdad Science Journal, 2023)
Two homopolymeric and three copolymeric additives for base oil were synthesized using octyl acrylate (OA) and tert-butyl acrylamide (TBA) monomers. The two additives named P1 and P2 are the homopolymers of TBA and OA, respectively, whereas copolymeric additives named Co1, Co2, and Co3 were synthesized by varying the ratios of TBA:OA as 1:3, 3:1 and 1:1, respectively. The prepared polymers were characterized by Fourier Transform Infrared (FTIR). Based on the solubility of synthesized polymers in base oil and reactivity ratios of TBA/OA copolymer (0.222, 0.434) calculated by Fineman-Ross method, P2, Co1, Co2 and Co3 were selected to evaluate their performance as pour point depressant (PPD), viscosity improver (VII), and anticorrosion additives in base oil. Additives P2 and Co1 showed the best performance as (PPD) and (VII) whereas Co2 and Co3 revealed the best performance as anticorrosion additives. The flash point of base oil increased as a concentration of polymeric additives increased in the base oil. In addition to study the performance of synthesized polymers as lubricant additives, the capability of polymers for removing CuII from synthetic wastewater was also investigated. Different parameters such as pH of solution, contact time, and CuII concentration were changed in order to study their effect on adsorption capacity of polymers. Generally, polymers with high TBA content such as P1, Co2, and Co3 showed good performance in removing CuII.